2016
DOI: 10.5797/jnet.oa.2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise Stent-assisted Cerebral Aneurysm Coiling: Can Antiplatelet Therapy be Terminated after Neointima Formation with the Enterprise Stent?

Abstract: Objective: Patients who undergo Enterprise stent (ES)-assisted cerebral aneurysm coiling require long-term antiplatelet therapy (AT). Some studies have reported that cessation or modification of AT increases the risk of cerebral infarction.The aim of this study was to evaluate whether AT can terminated without increasing the risk of ischemic events among patients who have undergone ES-assisted cerebral aneurysm coiling. Methods:This study evaluated 9 with 11 unruptured aneurysms were confirmed to have neointim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Neurointerventionalists generally agree that the use of APT after SACE does not need to be lifelong. [8][9][10][11][12][13] A French national survey revealed that only 16% of centres prescribed lifelong APT after SACE. 13 Complete endothelialisation of the stent reduces the need for lifelong APT by ensuring a living, non-thrombogenic surface within the lumen of the parent artery and eliminating direct stentblood flow contact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurointerventionalists generally agree that the use of APT after SACE does not need to be lifelong. [8][9][10][11][12][13] A French national survey revealed that only 16% of centres prescribed lifelong APT after SACE. 13 Complete endothelialisation of the stent reduces the need for lifelong APT by ensuring a living, non-thrombogenic surface within the lumen of the parent artery and eliminating direct stentblood flow contact.…”
Section: Discussionmentioning
confidence: 99%
“…27 Although previous retrospective studies predominantly relied on descriptive results, they proposed diverse regional protocols (3-24 months) for the safe timing for discontinuation of APT after SACE. [8][9][10][11][12] All of these protocols emphasised the selection of patients with a low risk of ischaemia and documented complete neointimalisation of the parent artery. [8][9][10][11][12] In line with the previous studies, our study findings suggest that APT benefits cerebral infarction prevention until 1 year after SACE, [8][9][10][11][12][13] making it a reasonable strategy to consider discontinuing APT at that time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until the stent surface is covered by the neointima, metal exposure activates platelets, leading to thrombus formation; therefore, to prevent delayed ischemic complications, it is necessary to continue DAPT for a specific period. 2 , 21 , 22) Regarding this period, no guidelines or consensus has been established, but a previous study reported that continuous DAPT for 9 months significantly reduced the incidence of ischemic complications without increasing the incidence of hemorrhagic complications. 4) We aim for the termination of antiplatelet therapy approximately 1 year after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that AT termination at least 6 months postoperatively did not result in ischemic events among patients with neointima formation after ES-assisted cerebral aneurysm coiling. 5) This suggests that, if neointima formation occurs after stent placement, AT can be terminated without ischemic events. Recently, the LVIS stent (LS; Low-profile Visualized Intraluminal Support device: MicroVention TERUMO, Tustin, CA, USA) has been available for cerebral aneurysm treatment in Japan as a new design braided stent that enables excellent wall apposition due to manipulation even if the parent artery is tortuous, like the carotid siphon (Fig.…”
Section: Introductionmentioning
confidence: 99%